Arc Crust Formation of Lesser Antilles Revealed by Crustal Xenoliths from Petit St. Vincent. (4th April 2022) - Melekhova, Elena; Camejo-Harry, Michal; Blundy, Jon; Wallis, Simon R; Annen, Catherine; Kunz, Barbara E; Jenner, Frances E; Thirlwall, Matthew
Abstract: The Lesser Antilles volcanic arc is known for its magmatic diversity and unusually abundant plutonic xenoliths. Xenoliths from Petit St. Vincent (Grenadines' archipelago) are particularly interesting because of their textural and petrogenetic range. Here we combine petrographic observations, Electron Backscatter Diffraction (EBSD) analysis, major and trace element chemistry of xenoliths and lavas and geochemical and thermal modelling to explore the construction of arc crust beneath Petit St. Vincent. Petit St. Vincent xenoliths are dominated by calcic plagioclase, clinopyroxene and amphibole, and can be divided into two main categories, igneous and meta-igneous. Igneous xenoliths typically have cumulate textures; meta-igneous xenoliths range texturally from those that preserve vestiges of primary magmatic fabrics to intensely deformed varieties characterised by grain-size reduction and foliation development. Meta-igneous xenoliths also contain the most calcic plagioclase (An98–100 ). The presence of both meta-igneous and igneous xenoliths provides evidence for reworking of older arc crust and antecedent igneous intrusions. The latter have a protolith composition similar to high-MgO, low-Sr picrites and high-Ca, high-Sr ankaramites from the neighbouring islands of Petite Martinique and Grenada. The meta-igneous xenoliths derive from older, mafic arc crust present at the onset of subduction. Trace element chemistry and EBSD analyses of meta-igneous xenoliths are consistent with a complex history of re-melting and deformation mediated by chlorine-bearing H2 O rich fluids (including melts). Thermal modelling supports crustal reworking through repeated magma intrusions and indicates that the observed thermal structure and thickness of crust beneath Petit St. Vincent could have developed on a timescale of approximately 4 million years at rates compatible with the regional arc magma flux. Based on evidence from thermodynamic models and exhumed ancient arc crust sections, Collins et al. ( Nature Geoscience, 13, 331–338, 2020 ) have proposed that water-fluxed melting may be an important aspect of deep arc crust sections world-wide. Textures and mineralogy of xenoliths from Petit St. Vincent, including their characteristic high-An plagioclase, testify to such a process beneath an active, intra-oceanicarc.